The Effect of Giving Black Rice Extract Ointment (Oryza Sativa L. Indica) on the Growth of Wistar Rat (Rattus Novergicus) Hair Follicles - Nancy Kartini; Cindy Denhara Wijaya; Andri Hidayat (CV. Inara, 2024)
Hair loss affects many people worldwide. Hair loss is common and can be treated with vitamins and minerals. Black rice (Oryza sativa l. indica) contains phenolic and anthocyanin-rich flavonoids. The study examined whether black rice extract ointment accelerated Wistar rat (Rattus norvegicus) hair follicle growth. This was an actual experiment with 30 mice. The research involved acclimating test animals in the lab, manufacturing black rice extract, and making ointment. After an Ointment Evaluation Test, Phytochemical Screening was performed. Test the FT-IR Functional Group. DPPH testing will determine antioxidant activity. Finally, four groups (control group, treatment groups 1, 2, and 3 with 10%, 20%, and 30% ointments) received treatment for 21 days. Study results were handled using SPSS. The normality test showed 0.652 > 0.05 significance, while the Independent Samples T-Test showed 0.00 < 0.05 significance. Alkaloids, flavonoids, tannins, and steroids/triterpenoids make black rice an antioxidant, according to the active compound test. For average hair growth, 10% black rice ointment dose therapy yielded 0.681 cm, 20% 0.769 cm, and 30% 0.851 cm. The study found that black rice extract contains high antioxidants (ppm concentration value <50) that can prevent premature skin aging and promote hair and skin health.